Endoscopic diagnosis of chronic diarrhea. Issue 1 (28th September 2021) - Kinoshita, Yoshikazu; Ariyoshi, Ryusuke; Fujigaki, Seiji; Tanaka, Katsuhide; Morikawa, Teruhisa; Sanuki, Tsuyoshi
Abstract: The prevalence of chronic diarrhea in the general population is reported to be 4%–5%. Since various pathological conditions cause diarrheal symptoms, etiological diagnosis of chronic diarrhea is difficult in many cases. Medical history taking, physical examinations, and laboratory testing are not adequately sensitive or specific, thus a colonoscopic investigation is frequently employed for etiological evaluation. However, for cases with non‐bloody chronic diarrhea, the diagnostic yield of a colonoscopy procedure is reported to be not high enough. Furthermore, endoscopically identifiable findings are not adequately specific for the diagnosis of diarrheal disease, except for inflammatory bowel disease, while microscopic colitis, amyloidosis, eosinophilic gastroenteritis, celiac disease, and bile acid diarrhea are difficult to definitively diagnose using endoscopic findings. Thus, a histopathological examination of biopsy samples obtained with endoscopy is critically important. Endoscopists should consider obtaining biopsy samples from even normal‐appearing gastrointestinal mucosa for chronic diarrhea diagnosis.